Attentional bias toward negative and positive pictorial stimuli and its relationship with distorted cognitions, empathy, and moral reasoning among men with intellectual disabilities who have committed crimes. Issue 1 (17th June 2020) - Sadek, Susan A.; Daniel, Matthew R.; Langdon, Peter E.
Abstract: The aims of this study were to examine: (a) whether men with intellectual disabilities who have a history of criminal offending attend to affective pictorial stimuli in a biased manner, and (b) whether there is a relationship between an affective attentional bias and offense‐supportive cognitions, empathy, and moral reasoning. Forty‐six men with intellectual disabilities who had a documented history of criminal offending, and 51 men who also had intellectual disabilities, but no such history, were recruited and asked to complete a computer‐based dot‐probe task using affective pictorial stimuli with randomization, along with measures of distorted cognitions, empathy, and moral reasoning. Those with a history of criminal offending endorsed significantly more offense‐supportive cognitions, had significantly lower general empathy, and more "mature" moral reasoning, as well as a significant attentional bias toward affective pictorial stimuli. Attentional bias significantly predicted offense‐supportive cognitions, and vice versa, having controlled for offense history, and Full‐Scale IQ, but this was not the case for empathy or moral reasoning. While the findings require replication, interventions that aim to modify attention bias with this population should be tested.